De Zuid-Amerikaanse aal. Twee vroege brieven uit de Nederlandse koloniën over dierlijke elektriciteit - Koehler, P.J. (Studium, 2008)
The South-American eel. Two early letters on animal electricity from the Dutch colonies Speculations about the nature of nerve action, including animal spirits, date back to antiquity. Only during the 18th century, when it became possible to store electricity in Leyden jars, did natural philosophers begin to realise that the sensations caused by electric fish are like those produced by these primitive capacitors. The important roles played by amateur observers in the Dutch colonies of South-America, and how they communicated with more established Dutch scientists in the Netherlands, are often relatively overlooked in histories of how the nerves became electrical. In this article we examine two mid-18thcentury letters from South-America to the Netherlands. Both dealt with what would soon be called the electric eel, and were published in the proceedings of the first Dutch Society of Science (in Haarlem). The discovery of the electric nature of the shocks produced by these fish in particular proved to be a crucial step in understanding animal electricity and the true nature of neurophysiology.